Community Development of Lampineung Village Through Making Anti-Mosquito Aerosol From Nutmeg Seeds (Myristica fragrans Houtt.): Pembinaan Masyarakat Desa Lampineung Melalui Pembuatan Aerosol Anti Nyamuk Dari Biji Pala (Myristica fragrans Houtt.) - Dina Kali Kulla, Periskila; Meilina, Rulia; Andika, Fauziah (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The incidence of dengue has increased dramatically worldwide in recent decades. Modeling estimates suggest 390 million dengue virus infections per year (95% credible interval 284-528 million), of which 96 million (67-136 million) manifest clinically. Efforts or ways to guard against mosquito bites are to keep the environment clean and use environmentally friendly mosquito repellent materials. One of the plants that can be used as a source of natural mosquito repellent is the nutmeg plant. The purpose of this activity is to empower the community in Lampineung village in making anti-mosquito aerosols from nutmeg seeds. Methods: Community service activities carried out from July to October 2024, with a total of 10 non-productive people in Lampineung village. The housewives were given education and also training in making an anti-mosquito aerosol from nutmeg seeds. Results: the process of making aerosols from nutmeg seeds not only improves community skills in processing local resources, but also opens up new business opportunities that are environmentally friendly. The results of this program show an increase in the knowledge and skills of the Lampineung Village community in processing the potential of local natural resources into useful products. The anti-mosquito aerosol made from nutmeg seeds is not only environmentally friendly but also provides economic opportunities for the community, especially in the context of local economic empowerment. This activity concludes that it has a positive impact on increasing community capacity, both in terms of economy, health, and environmental awareness, thus making a real contribution to the empowerment of the Lampineung Village community.